The importance of human resources to the innovative capacity of portuguese firms - Silva, Armando (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
In this study I test the importance of several Human Resource variables to the innovation capacity of portuguese firms but also the effects that the innovation process generates on Human Resources. A branch of the innovation literature states that the ability of firms to innovate relies on an innovative capacity, which, in turn, depends on several factors, both internal and external to enterprises. One of those factors is the effort of firms to train their personnel specifically in order to enable them to innovate. The present test is applied to 4818 Portuguese enterprises for the period 2002-2004 through the use of the fourth Community Innovation Survey data. In order to evaluate the contribution of Human Resources to innovation I have estimated several knowledge Production Functions, mainly using probits and tobits. In that framework it is assumed that innovation depends on some inputs (as the training of personnel) and on information-flows from the existing knowledge stock (as clients). I have found significant the role of personnel training for the innovative process of Portuguese firms. Moreover, I also found that the lack of qualified personnel hinged critically more innovative performance of firms and, in addition, it is noticed that the improvement of productivuty (cost reduction) was the main effect of innovation in Portuguese firms.